2020
DOI: 10.5551/jat.50187
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals of Serum Non-Cholesterol Sterols by Gender in Healthy Japanese Individuals

Abstract: The present study was conducted to establish a practical method for measuring non-cholesterol sterols and reference intervals of serum levels. Methods: Healthy subjects (109 men and 151 women), four patients with sitosterolemia, and 10 heterozygous mutation carriers of ABCG5/ABCG8 genes were investigated. Then, three non-cholesterol sterols (sitosterol, campesterol, and lathosterol) of fasting serum samples were measured via a practical and highly sensitive gas chromatography (GC) method with 0.2 µg/mL as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Previous studies have reported that high cholesterol absorption had higher risks for CVD in a prospective cohort 9) or case-control 10) studies, suggesting that high cholesterol absorption is a risk and absorption, respectively, by gas chromatography at SRL Inc., Tokyo, Japan. The procedure of gas chromatography has been described elsewhere in detail 25) . In brief, 200 μL of serum was transferred to a glass tube, and the mixed solution of 2.5 mL of 1 M NaOH and ethanol was added.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that high cholesterol absorption had higher risks for CVD in a prospective cohort 9) or case-control 10) studies, suggesting that high cholesterol absorption is a risk and absorption, respectively, by gas chromatography at SRL Inc., Tokyo, Japan. The procedure of gas chromatography has been described elsewhere in detail 25) . In brief, 200 μL of serum was transferred to a glass tube, and the mixed solution of 2.5 mL of 1 M NaOH and ethanol was added.…”
Section: Introductionmentioning
confidence: 99%
“…This process was repeated until exception data were not found any longer. 13 In addition, 2.5-97.5 percentiles of sdLDL-C and sdLDL-C/LDL-C as the reference intervals by a non-parametric analysis were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients theoretically should avoid foods rich in plant sterol. 1 Pharmacotherapy aimed at suppressing the absorption of plant sterol with ezetimibe and enhancing its excretion with biliary sequestrants such as colestimide is recommended. Statins can reduce LDL-C levels in sitosterolemic patients, although their effects may be limited.…”
Section: Discussionmentioning
confidence: 99%